2012
DOI: 10.1117/1.jbo.17.8.086011
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal recording of brain activity in term newborns during photic stimulation by near-infrared spectroscopy and electroencephalography

Abstract: In this study 14 healthy term newborns (postnatal mean age 2.1 days) underwent photic stimulation during sleep on two different days. Near-infrared spectroscopy (NIRS) and electroencephalography (EEG) was acquired simultaneously. The aims of the study were: to determine (i) the sensitivity and (ii) the repeatability of NIRS to detect the hemodynamic response, (iii) the sensitivity and (iv) the repeatability of EEG to detect a visual evoked potential (VEP), (v) to analyze optical data for the optical neuronal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The remaining six studies employed a stroboscopic light to elicit a visual response. The studies show similar results for Δ[HbO 2 ], with most studies observing a positive change in this parameter apart from Kusaka et al ( 2005 ) who observed a negative Δ[HbO 2 ] and Biallas et al ( 2012 ) who observed both positive and negative Δ[HbO 2 ]. Kusaka et al ( 2005 ) additionally observed an increase in Δ[HHb].…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…The remaining six studies employed a stroboscopic light to elicit a visual response. The studies show similar results for Δ[HbO 2 ], with most studies observing a positive change in this parameter apart from Kusaka et al ( 2005 ) who observed a negative Δ[HbO 2 ] and Biallas et al ( 2012 ) who observed both positive and negative Δ[HbO 2 ]. Kusaka et al ( 2005 ) additionally observed an increase in Δ[HHb].…”
Section: Resultssupporting
confidence: 67%
“…Nine fNIRS studies used visual stimulation. Visual stimuli generally used either a checkerboard pattern (Meek et al, 1998 ; Liao et al, 2010 , 2012 ) or a stroboscopic light (Hoshi et al, 2000 ; Taga et al, 2003 ; Kusaka et al, 2005 ; Karen et al, 2008 ; Biallas et al, 2012 ; Shibata et al, 2012 ). All studies monitored the occipital lobe, with some studies additionally monitoring the frontal lobe (Taga et al, 2003 ) and temporal and parietal lobe (Shibata et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous fNIRS studies by our group, we demonstrated the ability to measure evoked hemodynamic changes in the occipital cortex after visual stimulation in term-born neonates within their first days of life. [18][19][20] However, the development of the HRF pattern in the human brain remained unclear; some fNIRS studies reported an inverted HRF pattern (i.e., a decrease in blood flow or [O 2 Hb]) in young infants in response to perceptual stimuli, whereas some studies did not. 2,21,22 This has been a controversial issue, and investigations about this aspect in preterm-born neonates are particularly sparse, partly because the investigation of HRFs of these neonates using fNIRS is a relatively new subject.…”
Section: Introductionmentioning
confidence: 99%
“…This result highlights the need for integrated brain monitoring in newborns. As for sensory stimuli, a combined approach can also be successfully applied to investigate the newborn cerebral responses to stimuli obtained with other modalities, for example, visual responses during photic stimulation, 121 as well as to monitor the brain ability of sensory processing during normal development, such as acoustic processing in infants within the first 6 months of life 122 …”
Section: Combined Fnirs–eeg: Advantages and Applicationsmentioning
confidence: 99%